Real Time Emergency Auto Parking System in Driver Lethargic State for Accident Preventing - Alsibai, Mohammad Hayyan; Syafiq Fauzi, Kamarulzaman; Hossam , Adden Alfarra; Naif, Yasir Hashim (EDP Sciences, 2017)
This paper is presenting a safety driving and accident preventing system which uses a vision sensor to detect driver drowsiness and lethargic states. The system notifies the driver in dangerous situations. Moreover, in case the driver is unable to conduct safe driving, emergency parking system is to be activated. The system comprises two stages. First is a drowsiness detection stage which uses a smartphone or a tablet computer as a processing unit. The second stage is the vehicle emergency parking control system which uses a microcontroller unit (MCU). The MCU is connected to an alarm system, hazard lights and a vehicle control interface. The experiment results showed realistic real time responses. Drowsiness detection processing time average is about 480 ms / frame. Alarming system is responding perfectly within 500 ms. Simulation results illustrate the effectiveness of the developed schemes for the auto parking system in real time. The average time from drowsiness detection to fully parking, if the vehicle is moving at the speed of 100 km/s, is about 15s.